The Steel Truss Tower (Derricks) Structure Evaluation In Buckling Analysis - Miftahul Iman (P3M- Politeknik Negeri Kupang, 2020)
Tarakan was an oil-producing city had been known since 1896 that were explored in first time in authorized by Bataavishe Petroleum Maatchapij (BPM). The derrick was a petroleum drilling facility that were performed in steel truss structure. The derrick prototype had been modeled in 3D truss by utilizing SAP2000. The models had been classified into 2 models: perfect and imperfect models. The imperfections denoted by the percentage of elements loses (IM20, IM24), and IM16). Buckling analysis consisted in linear and nonlinear analysis had been evaluated. The 3D solid model (Abaqus) also performed for single element buckling. The results showed that perfect derrick model satisfied the strength and stability requirement . The percentage of element loss reduced the capacity 9.45%-37.83%. The IM16 model buckled at 4.27 T were based on nonlinear analysis and 18.50 T were based on linear analysis. The single elemen buckling was 20,63% of the largest compressive element